Pengaruh Informasi Pelayanan Prolanis dan Kesesuaian Waktu terhadap Pemanfaatan Prolanis di Pusat Layanan Kesehatan Unair - Auliya Firdha Chusna Arifa (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2018)
Background: The Chronic Disease Management Program (Prolanis) was a promotive and preventive program developed by BPJS Kesehatan in collaboration with Primary Health Care (FKTP). Target ratio of prolanis patient visit (RPPB) to FKTP in safe zone was at least 50% every month. Average range of RPPB at UnairHealth Service Center (PLK Unair) from January to July of 2017 was 15% out of 62 registered participants, still below the target of the safety zone determined by BPJS Kesehatan.Aims: This study aimed to analyze the influence of enabling factors and need factor for the utilization ofProlanis at PLK Unair.Method: This research was a correlational-analytic research by using cross sectional research design.Results: The result of this study showed that there was a significant influence between prolanis information (p=0,020) and time conformity (p=0,008) towards the utilization of prolanis in PLK Unair. Meanwhile, BPJS class, distance, travel time, availability of transportation, type of transportation, social relations, health workers,health facilities, waiting time, and need has no significant effect.Conclusion: The conclusion of this research is the utilization of prolanis in PLK Unair influenced by prolanis information and time conformity of the patients. PLK Unair needs to recollect the information of their patients, redesign the socialization media and conduct home visit as well as discuss the schedule of prolanis activitieswith the patients.Keywords: enabling factor, need factor, prolanis, utilization of health services